Development of thermo fluid heated double jacketed vat for manufacture of selected dairy product - Talwar, Gopika (Indian Journal of Dairy Science, 2018)
Indian dairy industry is dominated by small and unorganized dairy processing units. Processing of milk products at small scale is labour intensive resulting in non-efficient use of energy and non-uniform product quality. The processing equipment if available are of higher capacity and steam operated. At small scale milk processing require high investment and operation of boiler is not feasible. Therefore study was undertaken to modify an existing double jacketed vat for thermo fluid heating system. Two wet coil heaters of capacity 3 kW each were fitted in cavity of 4cm thickness. The shape of modified vat was frustum of cone with 3mm outer mild steel sheet and 3mm stainless sheet for inner bin. An agitator was employed with three blades for scrapping of the product manufactured. Two oils were tested (paraffin and silicon oil) for heat transfer medium in cavity of modified unit. Properties of thermo fluid like boiling point specific heat, rate of temperature rise were studied and paraffin oil was found to be more suitable thermo fluid.Â Silicon oil was observed to have lower smoke point of 166 o C so was not used for manufacture of heat desiccated product. Different volumes (10, 20 and 30 kg) of milk was taken to vat to study the effect of capacity, temperature distribution and it was found that maximum heat transfer. With 30 kg capacity and 20 liters of paraffin oil heat desiccated product basundi was prepared in modified vat and evaluated for color and sensory analysis. Basundi manufactured by modified vat scored 7.3 in overall acceptability to 7.7 of control sample. Total solids of basundi were calculated as 42% and in comparison to control sample, basundi prepared in MDJV had lower â€œlâ€ values and higher â€aâ€ andÂ â€œbâ€ value .